A Gelatin–Thrombin Matrix Topical Hemostatic Agent (Floseal) in Combination With Harmonic Scalpel Is Effective in Patients Undergoing Total Thyroidectomy: A Prospective, Multicenter, Single-Blind, Randomized Controlled Trial. (February 2016) - Docimo, Giovanni; Tolone, Salvatore; Conzo, Giovanni; Limongelli, Paolo; Del Genio, Gianmattia; Parmeggiani, Domenico; De Palma, Maurizio; Lupone, Gennaro; Avenia, Nicola; Lucchini, Roberta; Monacelli, Massimo; Gulotta, Gaspare; et al.
Background . Hemostasis during thyroidectomy is essential; however, the safest, most efficient, and most cost-effective way to achieve this is unclear. This randomized, multicenter, single-blind, prospective study evaluated the efficacy and safety of using different hemostatic approaches in patients undergoing total thyroidectomy. Methods . Patients aged ≥18 to 70 years were randomized to Floseal + a harmonic scalpel (HS), Floseal alone, HS alone, or standard total thyroidectomy. Primary endpoint was 24-hour drain output. Secondary endpoints included surgery duration and complications. Results . Two hundred and six patients were randomized to Floseal + HS (n = 52), Floseal alone (n = 54), HS alone (n = 50), and standard total thyroidectomy (n = 50). The 24-hour drain output was lower in the Floseal + HS group compared with standard thyroidectomy. Floseal + HS also had a shorter surgery time ( P < .0001) versus the other 3 treatments. Conclusion . Floseal + HS can be effective at reducing postsurgical drain output and provides a complementary hemostatic approach in patients undergoing total thyroidectomy.